Abundant Neural circRNA Cdr1as Is Not Indispensable for Retina Maintenance - Chen, Xue-Jiao; Li, Meng-Lan; Wang, Ya-Han; Mou, Hao; Wu, Zhen; Bao, Siqi; Xu, Ze-Hua; Zhang, Hang; Wang, Xiao-Yun; Zhang, Chang-Jun; Xue, Xiangyang; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2020)
Cdr1as is the most abundant circRNA in human and vertebrate retinas. However, the role of Cdr1as in the retina remains unknown. In this study, we aimed to generate a Cdr1as knockout (KO) mouse model and investigate the retinal consequences of Cdr1as loss of function. Through in situ hybridization, we demonstrated that Cdr1as is mainly expressed in the inner retina. Using CRISPR/Cas9 targeting Cdr1as, we successfully generated KO mice. We carried out ocular examinations in the KO mice until postnatal day 300. Compared with the age-matched wild-type (WT) siblings, the KO mice displayed mild changes in inner retinal thickness and ocular electrophysiological responses. Through small RNA profiling of the retinas, we determined that miR-7 was downregulated, while its target genes were upregulated. Taken together, our results demonstrated for the first time that Cdr1as ablation led to a mild retinal consequence in mice, indicating that Cdr1as abundance is not indispensable for retinal development and maintenance.